Respuesta :
x = -5/3 ; y = -4/3 (-5/3, -4/3)
x + y = -3
y = 2x + 2
Substitute y in the 1st equation by its value in the 2nd equation.
x + 2x + 2 = -3
3x = -3 -2
3x = -5
x = -5/3
*substitute the value of x in the 1st equation to the 2nd equation to find the value of y.
y = 2x + 2
y = 2(-5/3) + 2
y = -10/3 + 2
In adding fractions, make sure that the denominators are the same.
y = -10/3 + 2(3/3)
y = -10/3 + 6/3
y = (-10 + 6)/3
y = -4/3
x + y = -3
y = 2x + 2
Substitute y in the 1st equation by its value in the 2nd equation.
x + 2x + 2 = -3
3x = -3 -2
3x = -5
x = -5/3
*substitute the value of x in the 1st equation to the 2nd equation to find the value of y.
y = 2x + 2
y = 2(-5/3) + 2
y = -10/3 + 2
In adding fractions, make sure that the denominators are the same.
y = -10/3 + 2(3/3)
y = -10/3 + 6/3
y = (-10 + 6)/3
y = -4/3
x + y = −3
y = 2x + 2
Plug in equation 2 into equation 1.
x + 2x + 2 = -3
3x + 2 = -3
3x = -5
x = -5/3
There is only one answer choice that has x = -5/3, and that is (-5/3, -4/3).
Just to be sure, let's find the y-value.
y = 2x + 2
y = 2(-5/3) + 2
y = -10/3 + 2
y = -10/3 + 6/3
y = (-10+6)/3
y = -4/3
Your answer is B. (-5/3, -4/3).
y = 2x + 2
Plug in equation 2 into equation 1.
x + 2x + 2 = -3
3x + 2 = -3
3x = -5
x = -5/3
There is only one answer choice that has x = -5/3, and that is (-5/3, -4/3).
Just to be sure, let's find the y-value.
y = 2x + 2
y = 2(-5/3) + 2
y = -10/3 + 2
y = -10/3 + 6/3
y = (-10+6)/3
y = -4/3
Your answer is B. (-5/3, -4/3).